The Potential of Chrysin of Oroxylum indicum L. to Induce Carbonic Anhydrase (CA) to Improve Cattle Fertility - Amin, Mohamad; Fahmi, Muhammad Najib; Ridho, Muhammad Andi Ali; Fitri, Nurul; Lestari, Umie; Maulina, Dina; Amin, Ihya Fakhrurizal (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2020)
The Artificial Insemination (AI) aims to develop the potential of the cattle reproduction comprehensively. The success of AI results is highly dependent on the level of livestock fertility. Therefore, improv the quality and quantity of semen could be done by hormone induction. However, hormone prices are expensive. This problem could be overcome using alternative way with the natural compound containing chrysin which might has the same function. The purpose of the study was analyze the potential of chrysin compound from Bungli plant (Oroxylum indicum) as fertilizer of males through bioinformatics approach. Methods performed through data search by webserver with the following stages: (1) Pubchem, (2) Swiss (3) Target Prediction, (4) Uniprot, (5) Protein Data Bank and (6) docking software using PyRx, PyMOL and Discovery Studio. The results showed that the chrysin compound interact with carbonic anhydrase (CA) expressed from the testes of the cattle, through van der Waals and Pi-Alkyl bonds. Chrysin is effective as CA ligand inducers based on affinity bonds (-8.4 kcal/mole) and more negatively than flavonol as a control compound with binding affinity (-6.2 kcal/mol). This suggests that chrysin is an effective compound as a potential drug for improved livestock fertility.